Association between polycyclic aromatic hydrocarbon exposure and hypertension among the U.S. adults in the NHANES 2003–2016: A cross-sectional study - Lu, Lingyi; Ni, Rong (Environmental research, 2023)
The global burden of hypertension, the major cause of cardiovascular disease (CVD) globally, remains unresolved. Exposure to PM2.5 has been linked to hypertension (HTN) in adults and the elderly globally according to previous studies. Nonetheless, evidence on the association of polycyclic aromatic hydrocarbon (PAH) exposure and HTN risk in the general adult population in the United States was limited. To investigate the relationship between PAH exposure and HTN in adults in the United States, cross-sectional data during 2003 and 2016 from the National Health and Nutrition Examination Survey (NHANES) on a stratified multistage random sample of the civilian non-institutionalized population were utilized. After eliminating individuals with incomplete information of interest, the final analysis contained 8951 subjects aged ≥20. In the multivariate logistic regression model, 1-hydroxynaphthalene and 2-hydroxyfluorene were found positively associated with increased risk of HTN among overall participants after adjusting for the covariates. 1-hydroxynaphthalene and 2-hydroxynaphthalene showed positive associations with HTN risk among overweight participants. In the Bayesian kernel machine regression (BKMR) model, 1-hydroxynaphthalene and 2-hydroxyfluorene presented great importance to HTN risk among overall individuals. In the male subgroup analyses by BKMR, 2-hydroxyfluorene presented a positive effect on HTN risk when the remaining OH-PAHs were set at their 25th, 50th, and 75th percentile. Our findings highlight the complexities of estimating the risk of HTN associated with mixed PAH exposure, and additional longitudinal studies are required to determine the exact link between PAH exposure and HTN risk, as well as the underlying mechanisms. •Urinary 1-hydroxynaphthalene and 2-hydroxyfluorene were positively associated with HTN risk among overall participants.•2-hydroxyfluorene was found to have a positive relationship with an increased risk of HTN among males using BKMR.•1-hydroxynaphthalene was found to be positively associated with HTN risk among females.•1-hydroxynaphthalene and 2-hydroxynaphthalene were linked to an increased risk of HTN among overweight people.